Bioactive Composites in Dentistry: A Comparative Study of Tissue Regeneration, Biological Activity, and Clinical Outcomes in Various Dental Applications - Ikram, Amna Mehwish; Mohamad, Dasmawati; Shahzad, Aamir; Kausar, Rehana; Iqbal, Ayousha; Riaz, Amna (Journal of Neonatal Surgery, 2025)
Background: Bioactive composites represent a new generation of dental restorative materials that not only restore tooth structure but also actively participate in tissue regeneration and promote biological activity. Objective: To compare the tissue regenerative potential, biological activity, and clinical outcomes of various bioactive composite materials in various dental applications. Methods: A comparative cohort study was conducted at the Islam Dental College Sialkot, Pakistan, over 12 months from Jan, 2024 to December, 2024. A total of 144 participants with restorations or periodontal defects were included using consecutive sampling, divided equally between bioactive composite and comparator groups. In vitro assessments included microhardness, hydroxyapatite formation, calcium ion release, and pH changes at baseline, 1, 4, and 12 weeks. Data were analyzed using SPSS 25.0, with significance set at p ≤ 0.05. Results: Bioactive composites showed significantly higher microhardness (45.2 ± 5.8 vs. 28.7 ± 4.9 kg/mm²), hydroxyapatite formation (12.5 ± 2.1 vs. 5.8 ± 1.9 μm), calcium ion release (15.8 ± 3.4 vs. 4.2 ± 1.1 ppm), and pH elevation (p < 0.001) than comparators. Clinically, restoration retention (95.8% vs. 86.1%), marginal adaptation, periodontal defect fill (3.8 ± 0.6 vs. 2.5 ± 0.7 mm), and healing index scores were superior in the bioactive group, with fewer secondary caries. Conclusion: Bioactive composites enhance tissue regeneration, biological activity, and clinical performance, supporting their use as a reliable alternative to conventional materials in various dental applications.